Mentha piperita Linn.-a New Host of Alternaria tenuis Auct - Srivastava, A. K.; Srivastava, R. (Indian Forester, 1971)
A severe leaf blight of Mentha piperita Linn. Caused by Alternaria tenuis Auct. is described. Detailed description of the pathogen is given. Pathogenicity test revealed that A. tenuis Auct. Acts as a weak pathogen.